2009
DOI: 10.1111/j.1600-0560.2008.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

The current state of dermatopathology education: a survey of the association of professors of dermatology

Abstract: The majority of training programs use a variety of resources and mechanisms for teaching DP to dermatology residents. Some programs list barriers to DP education including lack of cases, microscopes, resident education time for DP-related teaching and availability of educators. We conclude that a greater depth and breadth of resources for DP education would be of benefit to dermatology residency programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 7 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…[26][27][28] The points in favor and in contention of this practice have been discussed at length, and the debate will continue. [26][27][28][29][30][31] Our interest is not in partaking in that discussion and our objective is not to endorse one group over another. Given that a large number of skin specimens are initially read by general pathologists, 1 our inclination lies in investigating the rates of discrepancies between histopathologic diagnoses rendered by general pathologists and dermatopathologists.…”
Section: Discussionmentioning
confidence: 98%
“…[26][27][28] The points in favor and in contention of this practice have been discussed at length, and the debate will continue. [26][27][28][29][30][31] Our interest is not in partaking in that discussion and our objective is not to endorse one group over another. Given that a large number of skin specimens are initially read by general pathologists, 1 our inclination lies in investigating the rates of discrepancies between histopathologic diagnoses rendered by general pathologists and dermatopathologists.…”
Section: Discussionmentioning
confidence: 98%
“…In 2009, 19.2% of dermatology residents used computerbased learning to study dermatopathology. 17 A survey of 132 dermatology and pathology residents found that 23% used virtual slide technology as a requirement in their training program and 71% used Internet image collections for reference and self-directed study. 12 Therefore, because a move toward virtual imaging seems apparent, we sought to investigate diagnostic accuracy and possible factors contributing to residents' preference for glass slides vs. virtual microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The total amount of time dedicated to the study of DP within dermatology residency programs is a testament to the importance of DP education and its valued impact on the development of well‐trained clinicians. Previously, it was estimated that 25% of the dermatology residency curriculum was devoted to DP teaching . However, a more recent survey of members of the Association of Professors of Dermatology found that, among the 52 respondent dermatology residency programs, approximately 30% of the training curriculum is now dedicated to DP education .…”
Section: Introductionmentioning
confidence: 99%